Integrated CO2 Capture and Utilization Using Non-Thermal Plasmolysis - Moss, Matthew; Reed, Daniel G.; Allen, Ray W. K.; Styring, Peter (Frontiers in Energy Research, 2017)
In this work, two simple processes for carbon dioxide (CO2) such as capture and utilization have been combined to form a whole systems approach to carbon capture and utilization (CCU). The first stage utilizes a pressure swing adsorption (PSA) system, which offers many benefits over current amine technologies. It was found that high selectivity can be achieved with rapid adsorption/desorption times while employing a cheap, durable sorbent that exhibits no sorbent losses and is easily regenerated by simple pressure drops. The PSA system is capable of capturing and upgrading the CO2 concentration of a waste gas stream from 12.5% to a range of higher purities. As many CCU end processes have some tolerance toward impurities in the feed, in the form of nitrogen (N2), for example, this is highly advantageous for this PSA system since CO2 purities in excess of 80% can be achieved with only a few steps and minimal energy input. Non-thermal plasma is one such technology that can tolerate, and even benefit from, small N2 impurities in the feed, therefore a 100% pure CO2 stream is not required. The second stage of this process deploys a nanosecond pulsed corona discharge reactor to split the captured CO2 into carbon monoxide (CO), which can then be used as a chemical feedstock for other syntheses. Corona discharge has proven industrial applications for gas cleaning and the benefit of pulsed power reduces the energy consumption of the system. The wire-in-cylinder geometry concentrates the volume of gas treated into the area of high electric field. Previous work has suggested that moderate conversions can be achieved (9%), compared to other non-thermal plasma methods, but with higher energy efficiencies (>60%).